Effects of Tai Chi on depression of middle-aged and older adults: an updated systematic review and meta-analysis - Lijuan Zeng; Xueyang Zhao; Yiqing Yu; Ting Hu; Chaoyang Li; Man Wu; Fen Yang (BMC, 2023)
Abstract Aim The objective of this study was to evaluate the efficacy of Tai Chi, a mind-body movement therapy originating from China, on depression in middle-aged and older adults. Methods A systematic search was conducted in seven databases (Embase, Cochrane, Medline, Wanfang, SinoMed, Weipu date, CNKI) for Randomized Controlled Trials (RCTs) published until Apr 16, 2023. The quality assessment, heterogeneity analysis, subgroup analysis, and sensitivity analysis of 12 RCTs selected from the literature were performed. Meta-analyses were conducted using RevMan 5.4 software. Results The study included 12 trials comprising 731 participants that met the inclusion criteria. The findings revealed that Tai Chi significantly improved depression in middle-aged and older adults [SMD = -1.21, 95% CI (-1.59, -0.83), I2 = 87.6%, P < 0.001]. Subgroup analysis revealed that the number of exercise weeks within the specified range, the total duration of exercise, and Tai Chi maneuvers had the greatest benefits on depression in middle-aged and elderly people. The results demonstrated that interventions lasting more than 24 weeks were more effective [SMD = -1.66, 95% CI (-2.28, -1.04), P < 0.05] than those lasting only 12 weeks [SMD = -0.73, 95% CI (-1.08, -0.38), P < 0.05]. The effect size was more significant when the total duration of the intervention was more than 2400 min [SMD = -1.31, 95% CI (-1.71, -0.92), P < 0.001], and when the 24-style Tai Chi exercise was selected [SMD = -1.06, 95% CI (-1.37, -0.75), P < 0.001], the difference was also statistically significant. Funnel plots combined with sensitivity analyses, Begg's and Egger's tests indicated no publication bias. Conclusion The study suggests that Tai Chi can be an alternative therapy for reducing depression in middle-aged and older adults. It is recommended to prolong the Tai Chi exercise period to more than 24 weeks, with a total exercise duration of more than 2400 min, and 24-style Tai Chi should be selected to achieve the best therapeutic effect in middle-aged and older adults with depression. It should be noted that there may be lower-quality studies in the RCT literature analyzed, which may limit the general applicability and credibility of the conclusions.